Notes on Afrotropical Catharsius species described by Edgar von Harold (Coleoptera: Scarabaeidae, Scarabaeinae) - Génier, François; Josso, Jean-François (Zootaxa, 2016)
The type material of the Afrotropical Catharsius species described by E. von Harold is studied. Lectotypes are designated for C. camillus, C. dux, C. harpagus, and C. pandion. Habiti, aedeagi and original labels of the primary types are illustrated. Catharsius mossambicanus Ferreira, 1960 is here considered a junior synonym of C. pandion Harold, 1877. An alloreferent male is designated and illustrated for C. dux Harold, 1878 in order to illustrate males of this species in which females are undistinguishable from C. duciformis Ferreira, 1959.